2022
DOI: 10.1140/epjs/s11734-022-00576-9
|View full text |Cite
|
Sign up to set email alerts
|

A multi-value 3D crossbar array nonvolatile memory based on pure memristors

Abstract: How to improve the storage density and solve the sneak path current problem has become the key to the design of nonvolatile memristive memory. In this paper, a high storage density and high reading/writing speed 3D crossbar array non-volatile memory based on pure memristors is proposed. The main works are as follows: 1) an extensible memristive cluster is proposed, 2) a memristive switch is designed, and 3) a 3D crossbar array non-volatile memory is constructed. The memory cell of the 3D crossbar array non-vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Sun et al [13] illustrated the implementation of a 3D crossbar array using purely memristive cells. The authors reported that the proposed 3D crossbar array nonvolatile memory has higher reading/writing speed, higher storage density, and lower power consumption.…”
Section: Circuit Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [13] illustrated the implementation of a 3D crossbar array using purely memristive cells. The authors reported that the proposed 3D crossbar array nonvolatile memory has higher reading/writing speed, higher storage density, and lower power consumption.…”
Section: Circuit Implementationmentioning
confidence: 99%
“…Additionally, the tools for memristor models should be diversified, such as fractional-order derivative, fractional-order difference, analog circuit, and digital circuits. Therefore, memristor-based studies are collected in this volume, including neural systems [1][2][3], multistability and hidden dynamics [4][5][6][7][8][9][10], synchronization controller [11,12], circuits [13][14][15][16][17][18], discrete memristor chaotic maps [19][20][21][22][23], and image encryption applications [24,25]. Some of the contributions discuss several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…A memristor is a non-linear resistor with memory characteristics, and its i-v characteristic curve is related to the frequency. Its proven good performance implies significant potential in the fields of chaotic circuits [3][4][5], nonvolatile memory [6,7], digital logic [8,9], artificial neural networks [10][11][12], and non-linear circuits. In general, the research of memristors includes physical implementation [2,13,14], applications in electronic circuits [15,16], and memristor emulators [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Sun et al [38] proposed a new 1T2M structure, which solves the sneak path current problem with one word line. Some scholars have tried to use all-memristor designs to realize the design of memory cells, such as the structure of 2M1M [39] and 2M2M [40], 2M is used to replace the transistor to realize the switching function, and avoid sneak path current, all-memristor designs increase the storage density, but the problem of sneak path current is inevitable. Therefore, how to improve the storage density while solving the sneak path current problem is the research focus of memristor memory.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works [38,40], an extensible memristive cluster structure enabling multi-value memory is proposed, which can improve the store density by adding memristors with different characteristics. On the basis of this work, this paper proposes a 4M memristive cluster, which is connected with a transistor to form a memory cell of a crossbar array, to realize a 4-bit multi-valued nonvolatile memory.…”
Section: Introductionmentioning
confidence: 99%